Molecular correlates and prognostic significance of SATB1 expression in colorectal cancer - Nodin Björn; Johannesson Henrik; Wangefjord Sakarias; O'Connor Darran P; Lindquist Kajsa; Uhlén Mathias; Jirström Karin; Eberhard Jakob (BMC, 2012)
Abstract Background Special AT-rich sequence-binding protein 1 (SATB1) is a global gene regulator that has been reported to confer malignant behavior and associate with poor prognosis in several cancer forms. SATB1 expression has been demonstrated to correlate with unfavourable tumour characteristics in rectal cancer, but its association with clinical outcome in colorectal cancer (CRC) remains unclear. In this study, we examined the prognostic impact of SATB1 expression in CRC, and its association with important molecular characteristics; i.e. beta-catenin overexpression, microsatellite instability (MSI) screening status, and SATB2 expression. Methods Immunohistochemical expression of SATB1 and beta-catenin was assessed in tissue microarrays with tumours from 529 incident CRC cases in the prospective population-based Malmö Diet and Cancer Study, previously analysed for SATB2 expression and MSI screening status. Spearmans Rho and Chi-Square tests were used to explore correlations between SATB1 expression, clinicopathological and investigative parameters. Kaplan Meier analysis and Cox proportional hazards modelling were used to explore the impact of SATB1 expression on cancer specific survival (CSS) and overall survival (OS). Results SATB1 was expressed in 222 (42%) CRC cases and negative, or sparsely expressed, in adjacent colorectal mucosa (n = 16). SATB1 expression was significantly associated with microsatellite stable tumours (p < 0.001), beta-catenin overexpression (p < 0.001) and SATB2 expression (p < 0.001). While not prognostic in the full cohort, SATB1 expression was significantly associated with poor prognosis in SATB2 negative tumours (HR = 2.63; 95% CI 1.46-4.71; pinteraction = 0.011 for CSS and HR = 2.31; 95% CI 1.32-4.04; pinteraction = 0.015 for OS), remaining significant in multivariable analysis. Conclusions The results of this study demonstrate that SATB1 expression in CRC is significantly associated with beta-catenin overexpression, microsatellite stability and SATB2 expression. Furthermore, SATB1 expression is a factor of poor prognosis in SATB2 negative tumours. Altogether, these data indicate an important role for SATB1 in colorectal carcinogenesis and suggest prognostically antagonistic effects of SATB1 and SATB2. The mechanistic basis for these observations warrants further study. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1922643082772076